UJI IN SILICO SENYAWA 2,6-DIHIDROKSIANTRAQUINON SEBAGAI LIGAN PADA RESEPTOR ESTROGEN ALFA - Felicia Fraulein Setiawan; Enade Perdana Istyastono (Sanata Dharma University, 2015)
Previous studies has shown that estrogen receptor alpha that binds to estrogen may increase cancer cell proliferation, thus estrogen receptor alpha can be targeted to cure breast cancer. The aim of this in silico study is to test whether phytoestrogen 2,6-dihydroxyanthraquinone is a ligand of estrogen receptor alpha. Setiawati et al. (2014) has established a valid protocol for Structure Based Virtual Screening using molecular docking software PLANTS 1.2. This protocol is used to test 2,6-dihydroxyanthraquinone as ligand for estrogen receptor alpha. Output from the protocol is analyzed using a post-docking analysis method developed by Istyastono (2015) in R 3.0.2. Visualization of binding pose is generated with PyMOL 1.2. Results show that 2,6-dihydroxyanthraquinone cannot be identified as a ligand of estrogen receptor alpha. The method used in this study is not suitable to identify 2,6-dihydroxyanthraquinone, which is a marginal active substance, as active ligand. Further study to develop a suitable method to identify marginal active substances as ligands in estrogen receptor alpha is needed.